2011
DOI: 10.1103/physrevb.84.241104
|View full text |Cite
|
Sign up to set email alerts
|

Driving magnetic order in a manganite by ultrafast lattice excitation

Abstract: At low-temperatures (T < T N =110 K < T CO/OO =220 K), single-layer La 0.5 Sr 1.5 MnO 4 exhibits CE-type charge, spin and orbital order, characterized by in-plane "zig-zag" ferromagnetic chains. These chains are antiferromagnetically coupled with one another, in and out of plane [11,12,13]. Resonant soft Xray diffraction is directly sensitive to this spin and orbital order, when the incident photon energy is tuned to the 2p→3d transitions (Mn L 2,3 edges), and provides both momentum-dependent and spectroscopic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
121
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 150 publications
(123 citation statements)
references
References 36 publications
(55 reference statements)
0
121
1
1
Order By: Relevance
“…Residual diffraction peak intensity for even the highest fluence is likely a result of a small misalignment between pump and probe beams and relatively similar spot sizes. At low fluences, the decay time appears to be nearly constant, but then decreases as the decay amplitude saturates with complete melting of the long-range magnetic order; extracted time constants range from 22.4 ps at the lowest fluence to 7.5 ps at the highest fluence, much slower than time constants of <1 ps recorded for melting of magnetic order in other materials [10,12,16]. …”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…Residual diffraction peak intensity for even the highest fluence is likely a result of a small misalignment between pump and probe beams and relatively similar spot sizes. At low fluences, the decay time appears to be nearly constant, but then decreases as the decay amplitude saturates with complete melting of the long-range magnetic order; extracted time constants range from 22.4 ps at the lowest fluence to 7.5 ps at the highest fluence, much slower than time constants of <1 ps recorded for melting of magnetic order in other materials [10,12,16]. …”
Section: Resultsmentioning
confidence: 93%
“…For example, we have recently shown that THz excitation can resonantly drive a magnon, which leads to a tilt of the spin cycloid structure in TbMnO3 due to magnetoelectric coupling [13]. In other materials, such as CuO or La0.5Sr1.5MnO4, it was observed that pumping with 800 nm light leads to an ultrafast suppression of magnetic order in less than 1 ps and that the magnetic phase transformation is delayed by approximately ¼ of the period of the low lying spin gap excitation [10,12]. Such ultrafast changes in magnetization (less than 1 ps) have also been observed in metallic ferromagnets via all optical pump/probe schemes and optical pump/XMCD (X-ray magnetic circular dichroism) probe experiments [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Switching has also been demonstrated in these materials using femtosecond optical excitation, at near-visible [9,10,11,12,13,14,15], mid-infrared [16,17,18,19,20], or THz [21,22,23] wavelengths.…”
Section: ! !mentioning
confidence: 99%
“…However, due to the lack of efficient ultrafast sources of direct magnetic excitation, the ultrafast magnetization dynamics in magnetically ordered materials was until recently initiated and controlled indirectly, using various optically activated mechanisms. For example, the inverse Faraday effect based on Raman-type nonlinear optical process, [2][3][4] dynamic momentum-space distribution of photoexcited spinpolarized carriers, 5 optical Stark effect, 6 thermal magnetic anisotropy change, 7 and lattice distortion 8 has been employed to excite the spin systems on femtosecond and picosecond timescales. In most of these cases, the spin excitation by ultrashort laser illumination of materials is accompanied by an undesirable thermal contribution, usually associated with electron dynamics that mediate the excitation of spin waves in the laser-induced process.…”
Section: Introductionmentioning
confidence: 99%